The photometric periods of rapidly rotating field ultra-cool dwarfs. Issue 1 (25th January 2023) - Miles-Páez, Paulo A; Metchev, Stanimir A; George, Benjamin
ABSTRACT: We use 1-m-class telescopes and the Transiting Exoplanet Survey Satellite ( TESS ) to explore the photometric variability of all known rapidly rotating ( v sin i ≳ 30 km s −1 ) ultra-cool (≥M7) dwarfs brighter than I ≈ 17.5 mag. For a sample of 13 M7–L1.5 dwarfs without prior photometric periods, we obtained I -band light curves with the SMARTS 1.3-m and WIYN 0.9-m telescopes and detected rotation-modulated photometric variability in three of them. Seven of our targets were also observed by TESS and six of them show significant periodicities compatible with the estimated rotation periods of the targets. We investigate the potential of TESS to search for rotation-modulated photometric variability in ultra-cool dwarfs and find that its long stare enables <80-h periodic variations to be retrieved with ≤1 per cent amplitudes for ultra-cool dwarfs up to a TESS magnitude of 16.5. We combine these results with the periods of all other known photometrically periodic ultra-cool dwarfs from the literature, and find that the periods of ultra-cool dwarfs range between 1 and 24 h, although the upper limit is likely an observational bias. We also observe that the minimum rotation periods follow a lower envelope that runs from ≈2 h at spectral type ≈M8 to ≈1 h at spectral type T.